Experimental and DFT studies of PM2.5 removal by chemical agglomeration. (15th January 2018) - Bin, Hu; Yang, Yi; Lei, Zhou; Ao, Shen; Cai, Liang; Linjun, Yang; Roszak, Szczepan
Highlights: Using DFT calculations to explore the internal interactions in ESP system at molecular level. Chemical agglomeration models is put forward by SEM. Experimental data and calculated data are consistent with particle agglomeration. Abstract: Fine particles are significantly harmful to the human body and the atmospheric environment. However, the electrostatic precipitator (ESP) removal efficiency for PM2.5 is low, therefore chemical agglomeration technology, which uses various chemical agents to induce particle agglomeration, improving the efficiency of ESP seems to be a promising pretreatment technology. In the present contribution a combination of experimental and DFT calculations has been used to study this technique. We used water, pectin and sodium alginate solutions as agglomeration agents. Experimental results showed that sodium alginate solutions is most effective, the particle diameter increased from 0.1 μm to 1 μm and the ESP removal efficiency of number concentration increased above 20% with chemical agglomeration technology. In theoretical studies we simulated various molecular clusters consisting of water, pectin and sodium alginate in combination with simple model silica particles (TOS) by using DFT calculations to explore the internal interactions in ESP system at molecular level. In our results, water, pectin and sodium alginate interacted with TOS by hydrogen bond, with interaction energy of 4.0 kcal/mol, 6.7 kcal/mol and 7.4 kcal/mol, respectively. Finally, according to the experimental and theoretical results, the chemical agglomeration models were put forward.